Uncovering the Obstacles Faced by Fifth-Grade Students in Solving Mixed-Operation Calculation Problems: A Perspective on Conceptual Understanding and Procedural Knowledge - Kartinah Kartinah; Dina Prasetyowati; Aries Tika Damayani (Journal La Edusci, 2026)
Fifth-grade students who experience obstacles when solving mixed calculation problems. The purpose of this study is to describe the obstacles in conceptual understanding and procedural knowledge experienced by fifth-grade students in solving mixed calculation problems. This study uses qualitative and methods was conducted at Public Elementray School Pandeanlamper 03, Semarang City with three research subjects using research instruments consisting of questions about mixed fraction calculations and interview guidelines to reveal the obstacles experienced by the subjects. The three subjects showed that they had organized their knowledge into a coherent whole, but the subjects where they are unable to see the relationship between concepts and procedures and are unable to provide arguments to explain why some facts are the result of other facts.